2023
DOI: 10.56827/seajmms.2023.1901.14
|View full text |Cite
|
Sign up to set email alerts
|

Chelo Index for Graphs

Abstract: It is exciting to study and establish relationships between the physical properties and the molecular structure of chemicals and there is a scope for defining new topological indices. This paper aims to introduce a new topological index for graphs called Chelo index. The Chelo index of a graph G is the sum of five times order of G and two times the number of geodesics of length 3 minus the number of geodesics between peripheral vertices. We compute Chelo index for some standard graphs and observe the correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…If the signs assigned to the edges depend on some property, the graph is called an induced sign graph. It is very natural to extend the theory of signed graphs into the algebraic graphs by assigning signs to the edges of algebraic graphs, and studies on such signed algebraic graphs (algebraic signed graphs) have been found to be of much interest (see [141,142]).…”
Section: Signed Graphs Based On the Unitary Cayley Graphsmentioning
confidence: 99%
“…If the signs assigned to the edges depend on some property, the graph is called an induced sign graph. It is very natural to extend the theory of signed graphs into the algebraic graphs by assigning signs to the edges of algebraic graphs, and studies on such signed algebraic graphs (algebraic signed graphs) have been found to be of much interest (see [141,142]).…”
Section: Signed Graphs Based On the Unitary Cayley Graphsmentioning
confidence: 99%